50 years of bat tracking: device attachment and future directions. Issue 4 (April 2014) - Teague O'Mara, M.; Wikelski, Martin; Dechmann, Dina K.N.; Fisher, Diana
Summary Radiotelemetry and satellite‐based telemetry approaches are essential to describe the behaviour and biology of animals. This is especially true for bats, whose small size and cryptic lifestyles make them challenging to study. However, only a handful of studies have evaluated how transmitter mass and the attachment method affect bat behaviour or health, and none have assessed the development of technical methods in the field. We review the past 50 years of bat tracking studies to determine how devices have been attached, how guidelines have been followed or changed, and whether any health or fitness impacts from these transmitters can be determined. Half of the nearly 300 studies available used devices heavier than the recommended 5% of body mass with minimal justification. Devices were typically glued directly to the backs of small bats and remained attached for 9 days. This is far shorter than battery life span of most devices. Little information is available regarding the overall impact of attaching transmitters on the health, survival and reproductive success of bats, and there has been little development in attachment methods since the first tracking studies. We consequently developed a collar for small bats with a degradable weak link and tested it on several species. The collar worked successfully on three of four species. This allows longer habituation and tracking times while ensuring that the device drops off after the battery expires. Future studies will need to invest more effort in assessing potential long‐term effects of tracking. They also need to build upon previous knowledge to find the best attachment method, size and shape for their study species to effectively improve wildlife tracking.